Analisis Determinan Pengangguran Terbuka di Provinsi Aceh: Studi Kasus 5 Kabupaten/Kota Tahun 2014-2023 (Jurnal Ekonomi dan Pembangunan Indonesia, 2025)
This study aims to determine the partial and simultaneous influence between the variables of labor force, the agricultural sector, economic growth, and the industrial sector on the open unemployment rate in Aceh Province in the 2014–2023 period. The research method uses a quantitative approach by utilizing secondary data obtained from related agencies. The results showed that the labor force variable (X1) had a significant influence on the open unemployment rate with a significance value of 0.000 < 0.05. The agricultural sector variable (X2) was also proven to have a significant effect with a significance value of 0.002 < 0.05. Furthermore, economic growth (X3) has a significant influence on open unemployment with a significance value of 0.004 < 0.05. The industrial sector variable (X4) also showed a significant influence on the open unemployment rate in Aceh Province with a significance value of 0.015 < 0.05. Overall, these results indicate that employment dynamics and regional economic structure play an important role in determining the open unemployment rate during the study period. These findings provide a basis for policymakers to formulate more effective economic development strategies in reducing unemployment in the future.